Interactive Physics Learning Innovation Using Solar System Scope to Understand Solar System Material - Widyaningtyas, Febrina Siska; Santoso, Fendi; Susilowati, Rina; Wibowo, Ghina Tamima; Agustin, Vita (Program Studi Pendidikan Fisika, 2025)
Physics learning is considered challenging because it involves abstract concepts that are difficult for students to understand, for example the material on the solar system. Interactive learning innovations use the Solar System Scope application as an effective learning medium in understanding the concept of the solar system. This study aims to describe the use of interactive web technology such as Solar System Scope as a learning medium for the solar system in class VI of Public Elementary School Suryodiningratan 3. The research approach uses qualitative descriptive with data collection techniques in the form of observation, interviews, and documentation. The results of the study showed that students were interested and found it easier to understand the material on the solar system. This innovation increases interest in learning, makes it easier to understand physics concepts, and encourages active student involvement in the learning process. The use of 3D visualization, interactive simulations, and exploration features allows students to learn the structure, motion, and characteristics of planets and the solar system in an interesting and amazing way. This innovation is expected to be an effective solution in supporting more modern and relevant physics learning.